2018
DOI: 10.1158/0008-5472.can-17-3454
|View full text |Cite
|
Sign up to set email alerts
|

A G3BP1-Interacting lncRNA Promotes Ferroptosis and Apoptosis in Cancer via Nuclear Sequestration of p53

Abstract: Long noncoding RNAs (lncRNA) have been associated with various types of cancer; however, the precise role of many lncRNAs in tumorigenesis remains elusive. Here we demonstrate that the cytosolic lncRNA P53RRA is downregulated in cancers and functions as a tumor suppressor by inhibiting cancer progression. Chromatin remodeling proteins LSH and Cfp1 silenced or increased P53RRA expression, respectively. P53RRA bound Ras GTPase-activating protein-binding protein 1 (G3BP1) using nucleotides 1 and 871 of P53RRA and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
331
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(341 citation statements)
references
References 54 publications
6
331
0
4
Order By: Relevance
“…Facilitates viral replication and assembly. [105,113] U. Alam, D. Kennedy BBA -Molecular Cell Research 1866 (2019) 360-370 activity of the p53 signalling pathway [43]. Regardless of their mechanism of action, both G3BP proteins inhibit p53 functions and hence play an accessory role in tumorigenesis.…”
Section: Results In Sgs Inhibition and Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facilitates viral replication and assembly. [105,113] U. Alam, D. Kennedy BBA -Molecular Cell Research 1866 (2019) 360-370 activity of the p53 signalling pathway [43]. Regardless of their mechanism of action, both G3BP proteins inhibit p53 functions and hence play an accessory role in tumorigenesis.…”
Section: Results In Sgs Inhibition and Viral Infectionmentioning
confidence: 99%
“…The interaction between G3BP2 and MDM2 compromises its ability to ubiquitinate p53 and the subsequent degradation of p53 by the proteasome [42]. A cytoplasmic lncRNA, P53RRA, interacts with the RRM domain (also responsible for the interaction of G3BP1 with p53) of G3BP1 in the cytoplasm via nucleotides 1 and 871 and this interaction displaces p53 from G3BP1-complex, subsequently retaining p53 in the nucleus, inducing cell cycle arrest and cell death [43]. P53RRA also increases the levels of MDM2 and p21 (which is a direct target of p53), showing that P53RRA promotes the…”
Section: G3bps and Tumour Suppressor Genesmentioning
confidence: 99%
“…For instance, lncRNA‐hPVT1 promotes cell proliferation, cell cycling, and stem cell‐like properties in hepatocellular carcinoma cells through binding to NOP2 and enhancing its stability . P53RRA lncRNA induces cell cycle arrest, apoptosis, and ferroptosis by binding with RAS GTPase‐activating protein‐binding protein 1, resulting in p53 retention in the nucleus . In this regard, we undertook ChiRP and mass spectrometry followed by RIP and identified UBA52 as a binding protein to LUCAT1 .…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition to lung cancer, LUCAT1 has also been reported to be involved in esophageal cancer, renal cell carcinoma, and cisplatin-resistant ovarian cancer. 17 27 In this regard, we undertook ChiRP and mass spectrometry followed by RIP and identified UBA52 as a binding protein to LUCAT1. UBA52, which is located on chromosome 19, is a hybrid gene encoding a fusion protein comprising ubiquitin at the N-terminus and RPL40 at the C-terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that lncRNAs play vital roles in multiple biological processes including proliferation, apoptosis, angiogenesis, drug resistance, and metastasis in various malignant tumors. [34][35][36][37][38] MALAT1 is a highly conserved lncRNA that was originally identified and is highly expressed in non-small-cell lung cancer. 39 MALAT1 presented diverse regulative functions on multiple malignant tumors including OS.…”
Section: Discussionmentioning
confidence: 99%